Outcome and Treatment of Nocardiosis After Solid Organ Transplantation: New Insights From a European Study. (4th February 2017) - Lebeaux, David; Freund, Romain; van Delden, Christian; Guillot, Hélène; Marbus, Sierk D.; Matignon, Marie; Van Wijngaerden, Eric; Douvry, Benoit; De Greef, Julien; Vuotto, Fanny; Tricot, Leïla; Fernández-Ruiz, Mario; et al.
Summary: In our study of 117 organ transplant recipients with nocardiosis, a history of tumor, invasive fungal infection, donor age, and no acute rejection were independently associated with 1-year mortality. Short-course antibiotic treatment (≤120 days), used in 17 patients, appeared promising. Abstract: Background: Solid organ transplant (SOT) recipients are at risk of nocardiosis, a rare opportunistic bacterial infection, but prognosis and outcome of these patients are poorly defined. Our objectives were to identify factors associated with 1-year mortality after nocardiosis and describe the outcome of patients receiving short-course antibiotics (≤120 days). Methods: We analyzed data from a multicenter European case-control study that included 117 SOT recipients with nocardiosis diagnosed between 2000 and 2014. Factors associated with 1-year all-cause mortality were identified using multivariable conditional logistic regression. Results: One-year mortality was 10-fold higher in patients with nocardiosis (16.2%, 19/117) than in control transplant recipients (1.3%, 3/233, P < .001). A history of tumor (odds ratio [OR], 1.4; 95% confidence interval [CI], 1.1–1.8), invasive fungal infection (OR, 1.3; 95% CI, 1.1–1.5), and donor age (OR, 1.0046; 95% CI, 1.0007–1.0083) were independently associated with 1-year mortality. Acute rejection in the year before nocardiosis was associated with improved survival (OR, 0.85; 95% CI, 0.73–0.98). Seventeen patients received short-course antibiotics (median duration 56 [24–120] days) with a 1-year success rate (cured and surviving) of 88% and a 5.9% risk of relapse (median follow-up 49 [6–136] months). Conclusions: One-year mortality was 10-fold higher in SOT patients with nocardiosis than in those without. Four factors, largely reflecting general medical condition rather than severity and/or management of nocardiosis, were independently associated with 1-year mortality. Patients who received short-course antibiotic treatment had good outcomes, suggesting that this may be a strategy for further study. Summary: In our study of 117 organ transplant recipients with nocardiosis, a history of tumor, invasive fungal infection, donor age, and no acute rejection were independently associated with 1-year mortality. Short-course antibiotic treatment (≤120 days), used in 17 patients, appeared promising.